The rose and the thistle ebook A novel. - Frantz, Laura (2023)
Amid the Jacobite uprising of 1715, an English heiress flees to the Scottish lowlands to stay with allies of her powerful family. But while castle walls may protect her from the enemy outside, a whirlwind of intrigue, shifting allegiances, and temptations of the heart lie within.